Modeling and animation of spring dynamic absorber: Fìz.-mat. model. ìnf. tehnol. 2021, 32:131-135 - Ignatyshyn, Mykola; Pelekh, Yaroslav; Hlynsky, Yaroslav; Pakholok, Bohdan (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2021)
The investigation of the action of the spring dynamic absorber, as well as the calculation of the physical quantities of the constructed model and animation, was carried out using non-linear methods of the Runge-Kutta type. Using only three references to the right-hand side of the differential equation, a method of the third order of accuracy is constructed, as well as two-sided approximations of the second order of accuracy. An explicit estimate of the error at each point of integration is given. References Bazhenov, V. A., Pohorelova, O. S., Postnikova, T. H. (2011). Rozvytok metodu prodovzhennya za parametrom dlya vibroudarnykh system pry modelyuvannya udaru syloyu kontaktnoyi vzayemodiyi. Opir materialiv i teoriya sporud, 87, 62-72. Sudak, F. M., Voronina, I. F., Altukhov, D. P. (2009). Zmenshennya shumu dvyhuniv vnutrishnʹho z•horyannya za dopomohoyu mekhanichnykh dempfernykh prystroyiv. DonNTU, 2(8), 98-101. Legeza, V. P., Legeza, D. V. (2008). Matematicheskaya model' dinamicheskoy sistemy s dvomassovym mayatnikom. Problemi prochnosti, 6, 100-109. Korneyev, B. G., Reznikov, L. M. (1988). Dinamicheskiye gasiteli kolebaniy. M.: Nauka. Animatsiya [Elektronnyy resurs].Information retrieval interaction. Retrieved from https://youtu.be/DjOpWkNjTdA Krylov, V. I., Bobkov, V. V., Monastyrnyy, P. I. (1977). Vychislitel'nyye metody. Tom II. M.: Nauka.